Tribological properties of friction composites modified by the suspended particles of exhaust flue gases - T. A. Akhmetov; V. K. Merinov; N. V. Kargapolova (Литьë и металлургия)
The possibility of using the deposited suspended particles of electric arc furnaces as heat-resistant modifying additives for friction composites is considered. It is shown that the precipitated particles obtained during the smelting of steel of different grades have identical morphology and are a homogeneous mechanical mixture consisting mainly of spherical particles of no more than 1 µm in size.It is established that the composites on the basis of the fluoropolymer, modified by precipitated particles obtained in the smelting of steel of various sizes have different tribological properties. This is due to the difference in the chemical composition of the deposited particles.It was found that the use of deposited particles in composite materials allows to vary the value of the dynamic friction coefficient in a wider range, in particular to obtain higher and stable values, while the wear resistance of modified friction composites is more than 500 times higher than the same index of the matrix polymer – polytetrafluoroethylene.